Human Body I - Editorial Sol 90 [et al.] (Chicago Encyclopaedia Britannica, Inc., 2011)
Explores the world of mammals, including their origin, evolution, types, habitats, life cycle, and relations with people.
Includes Glossary and Index.
Keywords: Human Body